2021
DOI: 10.1007/s10803-021-05266-4
|View full text |Cite
|
Sign up to set email alerts
|

General Education Teachers’ Perceptions of Autism, Inclusive Practices, and Relationship Building Strategies

Abstract: To identify target areas for professional development, this mixed-methods study examined general education teachers’ perceptions of autism and pedagogical practices in early elementary classrooms in the United States. In focus groups, teachers (N = 18) identified terms they associated with autism and strategies they used for inclusion and relationship building. Participants systematically free-listed and ranked their responses to three prompts. Using ranked responses, saliency scores were calculated to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…The results point towards a strong focus on strategies at the school level and foremost on implementing positive attitudes in teachers as a strategy to develop inclusive education for autistic students. Developing positive attitudes towards inclusive education is important, and there is a consensus that teacher attitudes are congruent with the effectiveness of inclusive education (Bolourian et al, 2021;Segall & Campbell, 2012) which we also identified. However, beyond positive attitudes, there is a need for finding strategies for the implementation of inclusive education.…”
Section: Discussionmentioning
confidence: 80%
“…The results point towards a strong focus on strategies at the school level and foremost on implementing positive attitudes in teachers as a strategy to develop inclusive education for autistic students. Developing positive attitudes towards inclusive education is important, and there is a consensus that teacher attitudes are congruent with the effectiveness of inclusive education (Bolourian et al, 2021;Segall & Campbell, 2012) which we also identified. However, beyond positive attitudes, there is a need for finding strategies for the implementation of inclusive education.…”
Section: Discussionmentioning
confidence: 80%
“…The current study illustrates how three kindergarten teachers gave meaning to the concept of inclusion through their play practices and strived to promote inclusion in a play-based learning framework. As they occurred in mainstream classrooms, strategies practiced by these teachers are likely to be considered acceptable and highly feasible, and those that align with previous empirical research could be incorporated into future teacher training opportunities (Bolourian et al, 2021 ). Overall, enactors provided insights into current understandings of inclusion in play-based learning, and what teachers may need going forward, to ensure that all children can be meaningfully supported and included in play.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers should also have the self-efficacy, techniques, knowledge, attitudes, and confidence to deal with the difficulties and aid students in understanding stigma [7,34,35]. The most significant concepts held by teachers concerning autism, such as social difficulties and narrow or fixed interests, demonstrated that they were aware of the main symptoms [36].…”
Section: Teachers Promote Equitable Education For Asd Studentsmentioning
confidence: 99%